Electromagnetic fields in nonuniform disk-loaded waveguides - Ayzatsky, M.I.; Mytrochenko, V.V. (Вопросы атомной науки и техники, 2016)
On the base of general approach we obtain some results that can be useful in the process of tuning of nonunifrom
disc-loaded waveguides. Our consideration has shown that simple values that characterize the detuning of the cells
can be introduced only for the disc-loaded waveguide with parameters that change very slow. In general case it is
needed to conduct full numerical simulation of specific disc-loaded waveguide and obtain all necessary coupling
coefficients. After that one can start the tuning process on the base of bead-pull field distribution measurements. На основе общего подхода получены результаты, которые могут быть полезны при настройке неоднородных диафрагмированных волноводов. Результаты анализа показали, что простые коэффициенты, которые характеризуют расстройку ячеек, могут быть введены только в случае медленного изменения параметров диафрагмированных волноводов. В общем случае необходимо провести полное математическое моделирование конкретного неоднородного диафрагмированного волновода и рассчитать необходимые коэффициенты связи. После этого можно проводить настройку ячеек, измеряя напряженность поля методом малого
возмущающего тела. На основі загального підходу отримано результати, які можуть бути корисними при настройці неоднорідних діафрагмованих хвилеводів. Результати аналізу показали, що прості коефіцієнти, які характеризують
розлад резонаторів, можуть бути введені тільки для випадку повільного змінення параметрів діафрагмованих хвилеводів. У загальному випадку необхідно провести повне математичне моделювання конкретного
неоднорідного діафрагмованого хвилеводу та розрахувати необхідні коефіцієнти зв’язку. Після цього можна
проводити налаштування резонаторів, вимірюючи напруженість поля методом малого збурювального тіла.